2023
DOI: 10.3390/vaccines11020343
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Attitude and Behavior among Nurses at a West Texas Regional Hospital

Abstract: Vaccinations against COVID-19 infection have become a contentious issue in the United States. Multiple segments of society, including healthcare workers, have expressed concerns regarding the need for vaccination and the safety of current vaccines. Many hospital-based nurses have helped care for patients with severe COVID-19 infections. An anonymous online survey was sent to the nursing staff at University Medical Center in Lubbock, TX, USA, through a hospital-based email system to determine vaccination status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The full prevalence of Covid-19 vaccine uptake among health workers at Nansana municipality stood at 81.6%, similar to a study about Covid-19 vaccine acceptance among health workers in rural Uganda (86.7% vaccine acceptance) [21]. Similarly, a survey conducted at West Texas hospital regarding Covid-19 vaccination attitudes and behaviors among nurses with prevalence above 80% [22] and a survey that assessed Covid-19 vaccine acceptability among health workers in Saudi Arabia with a full Covid-19 vaccine uptake of 91.4% [23].…”
Section: Prevalence Of Covid-19 Vaccine Uptakesupporting
confidence: 72%
“…The full prevalence of Covid-19 vaccine uptake among health workers at Nansana municipality stood at 81.6%, similar to a study about Covid-19 vaccine acceptance among health workers in rural Uganda (86.7% vaccine acceptance) [21]. Similarly, a survey conducted at West Texas hospital regarding Covid-19 vaccination attitudes and behaviors among nurses with prevalence above 80% [22] and a survey that assessed Covid-19 vaccine acceptability among health workers in Saudi Arabia with a full Covid-19 vaccine uptake of 91.4% [23].…”
Section: Prevalence Of Covid-19 Vaccine Uptakesupporting
confidence: 72%
“…Nursing staff indicated that protecting others’ health was the primary influential factor regarding COVID-19 vaccination, followed closely by the belief that the vaccine will prevent illness and concern for one’s health. Similarly, Peterson et al, 14 in a vaccination survey among another sample of nurses in West Texas hospitals, also found a protection motivation rather than the threat of job loss due to a mandate for COVID vaccination was the deciding factor for a highly vaccinated population of nurses. However, Peterson indicated that concerns over vaccine side effects were significant among unvaccinated nurses.…”
Section: Discussionmentioning
confidence: 88%